The Critical Role of PARPs in Regulating Innate Immune Responses - Zhu, Huifang; Tang, Yan-Dong; Zhan, Guoqing; Su, Chenhe; Zheng, Chunfu (Frontiers in Immunology, 2021)
Poly (adenosine diphosphate-ribose) polymerases (PARPs) are a class of proteins responsible for transferring ADP-ribose groups to target proteins to initiate the ADP-ribosylation, a highly conserved and fundamental post-translational modification in all organisms. PARPs play important roles in various cellular functions, including regulating chromatin structure, transcription, replication, recombination, and DNA repair. Several studies have recently converged on the widespread involvement of PARPs and ADP-Ribosylation reaction in mammalian innate immunity. Here, we provide an overview of the PARPs family and ADP-ribosylation's emerging role in regulating the host's innate immune responses involved in cancers, pathogenic infections, and inflammations, which will help discover and design new molecular targets for cancers, pathogenic infections, and inflammations.